Recent developments in supercritical fluid extraction of bioactive compounds from microalgae: Role of key parameters, technological achievements and challenges. Issue 36 (February 2020) - Molino, Antonio; Mehariya, Sanjeet; Di Sanzo, Giuseppe; Larocca, Vincenzo; Martino, Maria; Leone, Gian Paolo; Marino, Tiziana; Chianese, Simeone; Balducchi, Roberto; Musmarra, Dino
Highlights: Supercritical fluids (SCFs) are useful for microalgal compounds extraction. SCFs preserve the natural qualities of bioactive compounds minimizing energy costs. Pre-treatments of microalgae biomass could improve the subsequent SCFs extraction. Varying SCF temperature, pressure, flow rate, extract selectivity and purity change. SCF-CO2 extraction approach is promising for the recovery of thermolabile molecules. Abstract: Microalgae are a rich source of natural bioactive compounds, e.g. astaxanthin, β-carotene, lutein, and fatty acids (FAs), that are currently in high demand in the market. Conventional extraction methods often produce adverse effects on some of these compounds. Replacing conventional extraction methods with more efficient advanced green technologies that offer greater extracts purity and low environmental impact is therefore a challenging and sought-for target. This review is a comprehensive overview of supercritical fluid (SCF) extraction processes, including the latest research on the extraction of bioactive compounds from microalgae biomass and their benefits on human health. In addition, the role of key operating parameters on the selectivity of various compounds is discussed. This study provides useful knowledge that can productively contribute to the future development of SCF-based extraction technologies on an industrial scale.